Positive electrode material and preparation method and application thereof
The nickel-rich cobalt-free cathode material was prepared by hydroxide co-precipitation method, which solved the problems of fast attenuation of existing materials and poor thermal stability, achieved high energy density and excellent thermal stability, and improved the circulation life and safety of the material.
Patent Information
- Application Number
- CN202311406089.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-05-02
AI Technical Summary
The existing nickel-rich cobalt-free cathode materials have problems such as fast capacity decay and poor thermal stability, resulting in safety hazards and poor performance.
The nickel-rich cobalt-free cathode material LiNixMnyAl0.05Ti0.01Mg0.01Mo0.01O2 was prepared by hydroxide co-precipitation method. Through the co-precipitation and sintering steps, the chemical composition and synthesis conditions were controlled to improve the structural stability and thermal stability of the material.
The high energy density and excellent thermal stability of nickel-rich cobalt-free cathode materials are achieved, which significantly improves the cycle life and safety of the material.
Smart Images

Figure CN119920892A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a positive electrode material and a preparation method and application thereof, belonging to the field of electrochemical materials. Background Art
[0002] From the perspective of the global market where the sales of new energy electric vehicles are increasing year by year, it is mandatory to hope for a breakthrough in new energy electric vehicles. The development of new energy electric vehicles has been promoted under the impetus of the global market and policies. Among all the batteries on the market, lithium-ion batteries have become the focus of current research due to their advantages of low environmental pollution, high speed, long operation, affordability and lightness. Lithium-ion batteries are composed of positive electrodes, negative electrodes, diaphragms and electrolytes. Among them, raw materials account for the highest proportion of the cost of positive electrode materials, about 93%, and the energy density, cycle performance and rate performance of lithium-ion batteries mainly depend on positive electrode materials. Therefore, the key at present is to develop high-energy-density lithium-ion battery positive electrode materials. At present, the positive electrode materials of lithium-ion batteries on the market include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide and nickel cobalt aluminum oxide ternary materials. Among them, nickel cobalt manganese oxide ternary materials have obvious ternary synergistic effects and the highest energy density, and are widely used in various types of new energy passenger vehicles, bringing higher mileage and winning the favor of more and more people. However, due to the ethical issues of mining, regional resource restrictions, high cost and large price fluctuations of cobalt, people are eager to develop methods to eliminate cobalt without sacrificing the performance of cathode materials, which has promoted the development of nickel-rich cobalt-free cathode materials. However, nickel-rich materials have fast capacity decay and poor thermal stability, which can easily cause fire and even explosion hazards. It is very important to develop lithium-ion battery cathode materials with high energy density and good thermal stability. Summary of the invention
[0003] The purpose of the present invention is to provide a novel nickel-rich cobalt-free positive electrode material and a preparation method thereof in view of the deficiencies in the current technology. The prepared nickel-rich cobalt-free positive electrode material has high energy density and excellent thermal stability.
[0004] According to one aspect of the present application, a positive electrode material is provided, wherein the chemical formula of the positive electrode material is LiNi x Mn y Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2;
[0005] Among them, 0.6≤x≤0.8, 0.12≤y≤0.32.
[0006] According to another aspect of the present application, a method for preparing the above-mentioned positive electrode material is provided, comprising the following steps:
[0007] (1) co-precipitating an aqueous solution containing a metal salt, sodium hydroxide, and ammonia water to obtain a positive electrode material precursor;
[0008] The metal salts include metal nickel salts, metal manganese salts, metal aluminum salts, metal titanium salts, metal magnesium salts and metal molybdenum salts;
[0009] (2) The positive electrode material precursor obtained in (1) is mixed with a lithium salt and sintered to obtain the positive electrode material.
[0010] The metal nickel salt is selected from at least one of nickel sulfate and nickel nitrate;
[0011] The metal manganese salt is selected from at least one of manganese sulfate and manganese nitrate;
[0012] The metal aluminum salt is selected from at least one of aluminum sulfate and aluminum nitrate;
[0013] The metal titanium salt is selected from at least one of titanium sulfate and titanium nitrate;
[0014] The metal magnesium salt is selected from at least one of magnesium sulfate and magnesium nitrate;
[0015] The metal molybdenum salt is selected from at least one of molybdenum sulfate and molybdenum nitrate;
[0016] The dosage ratio is a stoichiometric ratio.
[0017] In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the concentration of metal ions in the metal salt is 1 to 2 mol / L;
[0018] In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the molar concentration ratio of the sodium hydroxide to the metal ion in the metal salt is 1.7 to 2;
[0019] In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the molar concentration ratio of the ammonia water to the metal ions in the metal salt is 2 to 2.5.
[0020] The coprecipitation temperature is 60-80°C.
[0021] The lithium salt is selected from at least one of lithium hydroxide and lithium carbonate;
[0022] The molar ratio of the lithium salt to the positive electrode material precursor is 1.05:1 to 1.1:1 (molar ratio).
[0023] The sintering atmosphere is an oxygen atmosphere;
[0024] The sintering is a two-stage sintering;
[0025] The first stage of sintering is to increase the temperature to 500-600℃ at 2-5℃ / min and keep it at that temperature for 5-6 hours;
[0026] The first stage of sintering is to increase the temperature to 750-800°C at 2-5°C / min and keep it at that temperature for 12-14 hours.
[0027] The positive electrode material precursor is mixed with the lithium salt and then ground for about half an hour.
[0028] Specifically,
[0029] Step 1: Prepare a mixed salt solution of sulfate salts of various transition metals in a stoichiometric ratio, and prepare sodium hydroxide and ammonia solution of a specific concentration as a precipitant and a chelating agent. Add the prepared solution into a reaction vessel for coprecipitation reaction, and the obtained solution is vacuum filtered and repeatedly washed with deionized water and then dried to obtain a precursor.
[0030] Step 2: Evenly mix the above-mentioned precursor and lithium salt to obtain a mixture.
[0031] Step 3: Heat the above mixture in an oxygen atmosphere to obtain the nickel-rich cobalt-free positive electrode material LiNi x Mn y Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2.
[0032] The reaction temperature is 60°C, the pH is 11, the stirring speed is 500 rpm, the synthesis atmosphere is argon, and the total concentration of the transition metal ion solution is 1 mol / L. The concentration of the sodium hydroxide solution is 2 mol / L, and the concentration of the ammonia solution is 1.67 mol / L. The selected transition metal solutions are all sulfate solutions.
[0033] According to another aspect of the present application, there is provided an application of the above-mentioned positive electrode material for lithium-ion batteries.
[0034] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0035] The doped elements have stronger bonding energy, so oxygen atoms or defects can be "trapped" around these elements, resulting in a reduction in oxygen atoms in the nickel redox center, alleviating the loss of oxygen, thereby enhancing the stability of the structure.
[0036] High nickel content ensures the high capacity of the material, and doping with other elements can improve the performance of the material in different ways. The effect of single-element doping is limited and may also cause certain side effects. By choosing multi-element (high entropy) doping, the interaction between different elements can be utilized to offset their adverse effects, maximize their advantages, and achieve the effect of 1+1>2. The present invention combines the advantages of NCM and NCA, and for the first time proposes a complex (high entropy) doping strategy of a new type of component to prepare a nickel-rich, cobalt-free layered positive electrode material with good structure, thermal stability, mechanical stability, and long cycle life.
[0037] The nickel-rich, cobalt-free lithium-ion battery positive electrode material prepared by the hydroxide co-precipitation method has the advantages of relatively uniform element mixing, simple synthesis conditions, low cost and short time, and is considered to be the most effective method for preparing ternary positive electrode materials.
[0038] The nickel-rich cobalt-free lithium ion battery positive electrode material of the present invention exhibits excellent stability. Within a wide voltage range of 2.5 to 4.4 V, the capacity retention rate is 95.63% after 100 cycles at C / 3. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The nickel-rich cobalt-free positive electrode material LiNi provided in Example 1 0.8 Mn 0.12 Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 XRD pattern of O2.
[0040] Figure 2 This is a test chart of the nickel-rich cobalt-free positive electrode material provided in Example 1, which was cycled 100 times at C / 3 current within the voltage range of 2.5-4.4V. DETAILED DESCRIPTION
[0041] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0042] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0043] Embodiment 1:
[0044] Nickel sulfate, manganese sulfate, aluminum nitrate, titanyl sulfate, magnesium sulfate, and molybdenum sulfate are prepared into a solution with a total transition metal concentration of 1 mol / L according to the stoichiometric ratio of Ni: Mn: Al: Ti: Mg: Mo = 0.8: 0.12: 0.05: 0.01: 0.01: 0.01, and stirred for 2 hours to mix them evenly. Then 200 mL, 2 mol / L sodium hydroxide and 200 mL, 2.5 mol / L ammonia solution are prepared as precipitants and chelating agents for the reaction, respectively. The prepared sodium hydroxide and ammonia solution are added to the transition metal solution through a peristaltic pump at a flow rate of 2 ml / min, while ensuring that the temperature is 60 ° C, the stirring speed is 500-600 rpm, the pH value is 11, and the reaction time is 5-6 hours. After the reaction is completed, the above solution is vacuum filtered, and washed with deionized water for reaction, and then dried in a vacuum drying oven at 110 ° C for 24-48 hours to obtain a precursor. Then, the obtained precursor and anhydrous lithium hydroxide with a molar excess of 5% were fully ground for 30 minutes and placed in a crucible with a lid. Then, in an oxygen atmosphere, it was heated to 500°C at a heating rate of 5°C / min, kept warm for 5 hours, and then heated to 750°C at a heating rate of 5°C / min, kept warm for 12 hours, and cooled with the furnace to obtain the nickel-rich cobalt-free positive electrode material LiNi 0.8 Mn 0.12 Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2 (abbreviated as NCM-8).
[0045] Figure 1 The nickel-rich cobalt-free positive electrode material LiNi provided in Example 1 0.8 Mn 0.12 Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 XRD pattern of O2. As shown in the figure, the sample has a clear rhombic α-NaFeO2 structure (R-3m space base), and no impurity phase is detected.
[0046] Embodiment 2:
[0047] Nickel sulfate, manganese sulfate, aluminum nitrate, titanyl sulfate, magnesium sulfate, and molybdenum sulfate are prepared into a solution with a total transition metal concentration of 1 mol / L according to the stoichiometric ratio of Ni: Mn: Al: Ti: Mg: Mo = 0.8: 0.12: 0.05: 0.01: 0.01: 0.01, and stirred for 2 hours to mix them evenly. Then 200 mL, 2 mol / L sodium hydroxide and 200 mL, 2.5 mol / L ammonia solution are prepared as precipitants and chelating agents for the reaction, respectively. The prepared sodium hydroxide and ammonia solution are added to the transition metal solution through a peristaltic pump at a flow rate of 2 ml / min, while ensuring that the temperature is 60 ° C, the stirring speed is 500-600 rpm, the pH value is 11, and the reaction time is 5-6 hours. After the reaction is completed, the above solution is vacuum filtered, and washed with deionized water for reaction, and then dried in a vacuum drying oven at 110 ° C for 24-48 hours to obtain a precursor. Then, the obtained precursor and anhydrous lithium hydroxide with a molar excess of 5% were fully ground for 30 minutes and placed in a crucible with a lid. Then, in an oxygen atmosphere, it was heated to 500°C at a heating rate of 5°C / min, kept warm for 5 hours, and then heated to 750°C at a heating rate of 5°C / min, kept warm for 12 hours, and cooled with the furnace to obtain the nickel-rich cobalt-free positive electrode material LiNi 0.7 Mn 0.22 Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2 (abbreviated as NCM-7).
[0048] Embodiment 3:
[0049] Nickel sulfate, manganese sulfate, aluminum nitrate, titanyl sulfate, magnesium sulfate, and molybdenum sulfate are prepared into a solution with a total transition metal concentration of 1 mol / L according to the stoichiometric ratio of Ni: Mn: Al: Ti: Mg: Mo = 0.8: 0.12: 0.05: 0.01: 0.01: 0.01, and stirred for 2 hours to mix them evenly. Then 200 mL, 2 mol / L sodium hydroxide and 200 mL, 2.5 mol / L ammonia solution are prepared as precipitants and chelating agents for the reaction, respectively. The prepared sodium hydroxide and ammonia solution are added to the transition metal solution through a peristaltic pump at a flow rate of 2 ml / min, while ensuring that the temperature is 60 ° C, the stirring speed is 500-600 rpm, the pH value is 11, and the reaction time is 5-6 hours. After the reaction is completed, the above solution is vacuum filtered, and washed with deionized water for reaction, and then dried in a vacuum drying oven at 110 ° C for 24-48 hours to obtain a precursor. Then, the obtained precursor and anhydrous lithium hydroxide with a molar excess of 5% were fully ground for 30 minutes and placed in a crucible with a lid. Then, in an oxygen atmosphere, it was heated to 500°C at a heating rate of 5°C / min, kept warm for 5 hours, and then heated to 750°C at a heating rate of 5°C / min, kept warm for 12 hours, and cooled with the furnace to obtain the nickel-rich cobalt-free positive electrode material LiNi 0.6 Mn 0.32 Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2 (abbreviated as NCM-6).
[0050] Comparative Example 1:
[0051] The commercial lithium nickel manganese oxide precursor material, chemical formula Ni 0.8 Co 0.1 Mn 0.1 (OH)2, and anhydrous lithium hydroxide were fully ground in an agate mortar at a molar ratio of 1:1.05 for half an hour. Then they were placed in a crucible and sintered in an oxygen atmosphere. The first sintering temperature was 350°C, the heating rate was 2°C / min, and the holding time was 5 hours. Then the temperature was raised to 750°C, the heating rate was 2°C / min, and the holding time was 12 hours. After cooling to room temperature, LiNi 0.8 Co 0.1 Mn 0.1 O2, named NCM811.
[0052] Figure 2 The electrochemical properties of Example 1 and Comparative Example 1 as positive electrode materials for lithium-ion batteries.
[0053] As shown in the figure, the electrochemical performance of the NCM-8 positive electrode material obtained in Example 1 is 95.63% in the voltage range of 2.5 to 4.4 V after 100 cycles of C / 3.
[0054] The electrochemical performance of the NCM811 positive electrode material obtained in Comparative Example 1 is that in the voltage range of 2.5 to 4.4 V, the capacity retention rate is 71.66% after 100 cycles of C / 3.
[0055] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A new positive electrode material, characterized in that: The chemical formula of the positive electrode material is LiNi x Mn y Al 0.05 Ti 0.01 Mg 0.01 Mo 0.01 O2; Among them, 0.6≤x≤0.8, 0.12≤y≤0.
32.
2. A method for preparing the positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) co-precipitating an aqueous solution containing a metal salt, sodium hydroxide, and ammonia water to obtain a positive electrode material precursor; The metal salts include metal nickel salts, metal manganese salts, metal aluminum salts, metal titanium salts, metal magnesium salts and metal molybdenum salts; (2) The positive electrode material precursor obtained in (1) is mixed with a lithium salt and sintered to obtain the positive electrode material.
3. The preparation method according to claim 2, characterized in that: The metal nickel salt is selected from at least one of nickel sulfate and nickel nitrate; The metal manganese salt is selected from at least one of manganese sulfate and manganese nitrate; The metal aluminum salt is selected from at least one of aluminum sulfate and aluminum nitrate; The metal titanium salt is selected from at least one of titanium sulfate and titanium nitrate; The metal magnesium salt is selected from at least one of magnesium sulfate and magnesium nitrate; The metal molybdenum salt is selected from at least one of molybdenum sulfate and molybdenum nitrate; The dosage ratio is a stoichiometric ratio.
4. The preparation method according to claim 2, characterized in that: In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the concentration of metal ions in the metal salt is 1 to 2 mol / L; In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the molar concentration ratio of the sodium hydroxide to the metal ion in the metal salt is 1.7 to 2; In the aqueous solution containing metal salt, sodium hydroxide and ammonia water, the molar concentration ratio of the ammonia water to the metal ions in the metal salt is 2 to 2.
5.
5. The preparation method according to claim 2, characterized in that: The coprecipitation temperature is 60-80°C.
6. The preparation method according to claim 2, characterized in that: The lithium salt is selected from at least one of lithium hydroxide and lithium carbonate; The molar ratio of the lithium salt to the positive electrode material precursor is 1.05:1 to 1.1:
1.
7. The preparation method according to claim 2, characterized in that: The sintering atmosphere is an oxygen atmosphere; The sintering is a two-stage sintering; The first stage of sintering is to increase the temperature to 500-600℃ at 2-5℃ / min and keep it at that temperature for 5-6 hours; The first stage of sintering is to increase the temperature to 750-800°C at 2-5°C / min and keep the temperature for 12-14 hours.
8. The preparation method according to claim 2 The positive electrode material precursor is mixed with the lithium salt and then ground.
9. An application of the positive electrode material according to claim 1, characterized in that: For lithium-ion batteries.
Citation Information
Patent Citations
Cationic composite doped ternary anode material for lithium ion battery and preparation method of material
CN109494352A
New doping strategy for layered oxide electrode materials used in lithium-ion batteries
US20220336802A1